Personality, intelligence, motivation and learning strategies in students of the CEPRE-UNMSM; 2013 entrants to San Marcos National University - Chávez Ch., Hilda J. (2015)
The present study, of descriptive nature, non experimental and cross-sectional, describes the dimensions of personality, intelligence, motivation and also learning strategies in 553 students of the CEPRE-UNMSM using Eynseck Personality Inventory Form B, D-70 Test and MSLQ-SF Questionnaire. The results indicate that the freshmen 2013 San Marcos tend to sanguine, because the G factor of intelligence places them in the top category, they have moderate anxiety and use, to learn, mostly using cognitive and metacognitive strategy development in resource management strategy better manage self-regulation effort and value components are intrinsically oriented to your goals. The purpose is to identify the psychological profile of the students, this allows the formulation of programs to orientate and/or reorientate the academic tasks of pre-university students.